La poètica de Carles Salvador i la generació de 1930 - Meseguer, Lluís B. (Caplletra. Revista Internacional de Filologia, 2015)
Meseguer situates Carles Salvador within the literary trends of his contemporaries. He deals with Salvador's implicit and explicit ideological influences, focusing on the poetics of various texts: El jazz, el maquinisme i la poesia pura (1928), Colps d'escut i de sageta (1929), Significado de Avantguardisme, his declaration in La poesia valenciana en 1930, and his unpublished paper El meu concepte de la poesia.